Recent Progress in Diatom Biosilica: A Natural Nanoporous Silica Material as Sustained Release Carrier - Hayeon Lim; Yoseph Seo; Daeryul Kwon; Sunggu Kang; Jiyun Yu; Hyunjun Park; Sang Deuk Lee; Taek Lee (MDPI AG, 2023)
A drug delivery system (DDS) is a useful technology that efficiently delivers a target drug to a patient's specific diseased tissue with minimal side effects. DDS is a convergence of several areas of study, comprising pharmacy, medicine, biotechnology, and chemistry fields. In the traditional pharmacological concept, developing drugs for disease treatment has been the primary research field of pharmacology. The significance of DDS in delivering drugs with optimal formulation to target areas to increase bioavailability and minimize side effects has been recently highlighted. In addition, since the burst release found in various DDS platforms can reduce drug delivery efficiency due to unpredictable drug loss, many recent DDS studies have focused on developing carriers with a sustained release. Among various drug carriers, mesoporous silica DDS (MS-DDS) is applied to various drug administration routes, based on its sustained releases, nanosized porous structures, and excellent solubility for poorly soluble drugs. However, the synthesized MS-DDS has caused complications such as toxicity in the body, long-term accumulation, and poor excretion ability owing to acid treatment-centered manufacturing methods. Therefore, biosilica obtained from diatoms, as a natural MS-DDS, has recently emerged as an alternative to synthesized MS-DDS. This natural silica carrier is an optimal DDS platform because culturing diatoms is easy, and the silica can be separated from diatoms using a simple treatment. In this review, we discuss the manufacturing methods and applications to various disease models based on the advantages of biosilica.